IOT-Based Smart Lamp Using Arduino - Diviandi Muhammad; Ghalib Eko Prasetyo; Muhammad Ferrizal Ramadhan; Antonius Suhartomo (President University, 2020)
This project is the application of IoT for home appliances, in particular lighting. The prototype is making use NodeMcu as the main controller and free to use IoT platform BLYNK. The combination of these two provides capabilities to control the lamp(s) remotely using smartphone connected to the Internet. The prototype uses Google Assistant to turn on and turn off the lamp remotely using voice command.